Comparison between single-diode and two diodes models of a grid connected PV technologies: numerical study and experimental validation - L. Bouhaki; R. Saadani; M. Rahmoune (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This article presents a simulation model comparison between a diode and two diodes of a photovoltaic cell. The simulation model created under the Matlab-Simulink environment predicts annual performances of the three photovoltaic field technologies connected to the grid. The simulation models have been validated by the experimental data of the photovoltaic system in the meteorological conditions of the city of Meknes. The interest is to inspect the closest model that allows to obtain more reliable results in order to follow the performances and the operation of the installation in the coming years, Also to compare between the efficiency of the three photovoltaic technologies (monocrystalline, polycrystalline and amorphous) in the same climatic conditions of Meknes city in Morocco which is a  Mediterranean climate with very cold winters and very hot summer.